STATE AND PROSPECTS OF AIRCRAFT FLIGHT SIMULATORS BUILDING - Апенько, Н.В. (Proceedings of National Aviation University, 2012)
Preparing astronauts, pilots, operators of complex systems on a live plant requires significant public expenditure. The alternative is to create air simulators and aircraft simulators, which are as much as possible close to existing facilities and allow those who are going through training to acquire stable skills piloting the corresponding objects. The use of simulators increases security in the preparation of pilots, leading to fuel savings and reduces pollution. The development of new domestic airline simulators, in turn, must rely on international experience in this area. Conduct a comprehensive analysis of the international status of this issue will draw on this time of experience in the further development of domestic aircraft simulators with enhanced capabilities of visualization systems and will contribute to saving the state to train personnel and increase its defense power as a whole.